The impact of the 1949 Chinese Revolution on a Latin American Chinese community: shifting power relations in Havana’s Chinatown - Manke,Albert (2018)
Abstract This article argues that, while initially constrained by U.S. Cold War policies both in the Americas and in Asia, China’s 1949 Communist Revolution could finally have a transformative impact on Latin American Chinese overseas community after the Cuban Revolution opened up new avenues for socialist influence in Latin America. By using new archival sources and interviews, we will analyze this changing impact by highlighting the intertwined layers of shifting power structures with a specific focus on the Chinese community in Cuba.